Making a Web-Based Service Request Management System Application at The Financial and Development Supervisory Agency (BPKP) - Sefulloh, Mohamad Cholid; Junaedi, Ifan; Sianipar, Anton Zulkarnain (Universitas Mohammad Husni Thamrin, 2025)
A company can store data quickly and securely using a computerized system rather than a manual one. The increasingly innovative and diverse development of technology today, and the difficulty of containing its development, makes all aspects of today's business dependent on computerized aspects that are integrated with the world of technology and informatics. Web-based information systems in Indonesia are increasingly being felt in supporting daily activities, both economic and non-economic. The Financial and Development Supervisory Agency (BPKP) requires a good network and server monitoring system to maintain the availability and performance of IT services. The problem faced is the lack of real-time visibility into the condition of the IT infrastructure, which can hinder early detection of system disruptions or anomalies. This study aims to design and implement a network and server monitoring system using Zabbix as an open-source solution that is able to monitor performance, availability, and provide automatic notifications when failures occur. The methods used include literature review, needs analysis, system architecture design, implementation of Zabbix Server and Agent, and system testing in the BPKP environment. The implementation results demonstrated that Zabbix was capable of providing comprehensive data visualization, real-time monitoring, and an effective alert system. In conclusion, the implementation of Zabbix successfully increased the efficiency of IT infrastructure management at BPKP and can serve as the basis for developing broader monitoring for all BPKP representatives.